Come on in : 15 stories about immigration and finding home - Alsaid, Adi; Azad, Nafiza; Farizan, Sara; Sugiura, Misa; Rivera, Lilliam; Johnson, Alaya Dawn, 1982-; Charaipotra, Sona; Andreu, Maria E.; Goo, Maurene; Bajaj, Varsha; Larbalestier, Justine; Quintero, Isabel; et al. (Inkyard Press, 2020)
This collection features stories from bestselling and up-and-coming YA authors.